Development of a Web-Based Document Archiving System for Local Government Using Laravel: A Software Engineering Approach - Abdullah Ardi; Adina Apriyani; Memed Saputra; Mega Wahyu Rhamadani (Journal of Renewable Energy and Smart Device, 2026)
Most local government digitization efforts fail to address workflow inefficiencies and lack structured governance mechanisms, limiting their operational impact. This study presents a governance-oriented web-based document archiving system built with Laravel MVC and Agile (Scrum), implemented at BKAD Kabupaten Kapuas. The key novelty lies in integrating role-based access control (RBAC), audit trails, and structured metadata management as core architectural elements  systematically restructuring document workflows rather than merely digitizing existing processes. Evaluation through functional testing, performance comparison, and user satisfaction analysis confirmed substantial operational improvements, including dramatic reductions in retrieval time and error rates, alongside near-perfect data completeness. User satisfaction consistently exceeded 4.3/5.0 across all dimensions, validating system usability across varying levels of digital literacy. The modular open-source architecture provides a replicable model for similar institutions, with direct implications for scalable and accountable e-government transformation.